Practice on the construction of ideological and political education in the basic nursing course (基础护理学课程思政建设的实践研究) - HUANG Tingting (黄婷婷) (中西医结合护理)
Objective To involve and evaluate the ideological and political education in the basic nursing course, improve the moral sentiments, occupational emotion, sense of value of nursing students and improve the quality of nursing talents training. Methods The ideological and political education, focusing on patriotism, sensation of life and humanistic feelings, was integrated into the basic nursing course. The ideological and political education was carried out by varies of methods such as students’ speech and sharing, teachers’ guidance and inspiration, case teaching, encouraged by advance models. Results After a semester course with ideological and political education, students’ ideological awareness, occupational values, professional quality had been improved. Conclusion The ideological and political education in the basic nursing course help to improve the ideological awareness, occupational values, professional quality of nursing students. (目的 在基础护理学课程教学中融入思政教育、开展课程思政, 探讨课程思政在本门课程中的实践效果, 培养护生的道德情操、职业情感、价值观, 提高护理人才培养质量。方法 在2018级护理专业2个班中开展基础护理学课程思政。通过 “家国情怀”、“生命情怀”、“人文情怀”三大主题教育, 与教学融合, 通过学生演讲与分享、教师引导与启发、案例教育、事迹感染等方法, 在理论、实训教学中贯穿课程思政。通过问卷调查、书写反思日记、访谈、护理行为观察法评价育人效果。结果 在一学期课程思政结束后, 学生思想觉悟、职业价值观、职业素养有了明显的提升, 对课程思政给予了充分的肯定和较高的评价。结论 基础护理学课程思政可提高护生的思想道德情操、职业情感、职业素养, 提升学生的视角, 发挥显著的育人效果。)